PREPARATION OF A NEW MOLECULARLY IMPRINTED POLYMERS AND ITS USE IN THE SELECTIVE EXTRACTION FOR DETERMINATION BROMHEXINE HYDROCHLORIDE AT PHARMACEUTICALS - & et al., Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed four electrodes were synthesized based on molecularly imprinted polymers (MIPs). Two MIPs were prepared by using bromhexine hydrochloride (BHH) as the template, acryl amide (AA) and methyl methacrylate (MMA) as monomers as well as ethylene glycol dimethacrylate (EGDMA) and penta erythritol triacrylate (PETA) as cross linkers respectively and benzoyl peroxide as initiator. The same composition was used in preparation of non-imprinted polymers (NIPs), but without the template (Bromhexine hydrochloride). To prepare the membranes, different plasticizers were used in PVC matrix such as: Di butyl sebacate (DBS), acetophenone (AP), di-octyl phthalate (DOPH) and tri-2-ethyl hexyl phosphate (TEHP). The characteristics studied are the slop, detection limit, life time and linearity range of BHH–MIPs electrodes. Results obtained of selectivity measurements on interfering cations (Al+3, Ca+2, K+) and some pharmaceutical additives such as methylparaben, propylparaben, trisodium citrate show that no interfering with drug bromhexine hydrochloride. The preparation electrodes have been shown good response including testing pharmaceutical analysis.